Englishness and empire, 1939-1965 - Webster, Wendy (Oxford University Press, 2005)
Did loss of imperial power and the end of empire have any significant impact on metropolitan culture and identity after 1939? Within a burgeoning literature on national identity and Englishness, this is a question that has received surprisingly little attention. Drawing on extensive research in the media archive, Wendy Webster's highly readable study investigates popular narratives of nation, and the significance of empire and its legacies in shaping national identity after 1939. What were the tensions and uncertainties involved in defining a post-imperial nation? How did imperial legacies inf.